Analysis of the Role of the Inspectorate in Improving the Accountability of Village Financial Management - Pahmi, Ahyar; Lubis, Maksum Syahri; Sembiring, Walid Musthafa (Journal La Sociale, 2025)
This study aims to analyze the role of the Inspectorate in increasing accountability for village financial management in Mandailing Natal Regency. Accountability in village financial management is essential to ensure that village funds are used transparently and effectively in accordance with village development goals. The research method used is qualitative with a case study approach, involving in-depth interviews, observations, and analysis of related documents. The results of the study show that the Mandailing Natal Regency Inspectorate has a significant role in supervising village financial management, including through financial audits, providing recommendations for improvement, coaching to village officials, and continuous supervision. However, this study also found several inhibiting factors that affect the effectiveness of supervision, including limited human resources (HR), limited budgets, lack of coordination between the Inspectorate and the village government, and low understanding of accountability at the village level. To increase the effectiveness of supervision, improvements are needed in these aspects, including increasing human resource capacity, more adequate budget allocation, and more intensive coaching at the village level. This study provides recommendations to increase the role of the Inspectorate in supervising village financial management to achieve more transparent and accountable management.